Performance Analysis of Off-Street Parking around the Central Business District of Akure Southwest Nigeria - Oyedepo, Joseph (Consilience, 2016)
Central Business Districts (CBD) are areas of dense traffic which result in parking problems. Four parks were selected for detailed study in Akure, the capital of Ondo State, Nigeria. Parking surveys were conducted to evaluate their parking index (efficiency) using both close and open-ended questionnaires. Parking index (efficiency) for OFP1, OFP2, OFP3 and OFP4 were obtained as 42.5%, 69.52%, 74.88% and 26.66% respectively. The study shows that OFP1 and OFP4 operated below the maximum capacity at parking index lower than 50%, while OFP2 and OFP3 operated above the maximum capacity when compared with Policy 7 of the Parking Space Requirements in Parking Code Guidance 2012 of San Francisco Department of Transportation. Furthermore,50%, 36% and 14% of the respondents affirmed that the facilities are not adequate, adequate and very adequate respectively. Inadequacy in parking signage and deficiency in enforcement by Management was observed. However, effective communication, parking enforcement, operational efficiency and provision of parking signage should be adopted in the study area.